Evaluation of Maturity Level of the Electronic based Government System in the Department of Industry and Commerce of Banjar Regency - Saputra, M. Rizeki Yuda; Winarno, Wing Wahyu; Henderi, Henderi; Shaddiq, Syahrial (Journal of Robotics and Control (JRC), 2020)
This research was conducted to determine the progress achieved and provide suggestions for the implementation of the EBGS service domain in the Banjar Regency Industry and Trade Office. The Electronic Based Government System (EBGS) assessment structure is specific to the Domain 3 EBGS service maturity level in the capability of the function and uses the Capability Maturity Model/Capability Maturity Model Integration (CMM/CMMI) Development method. The EBGS Service domain index calculation is based on the results of data processing from 12 respondents on the EBGS questionnaire, then CMMI Roadmap is mapped based on the EBGS service domain which has the highest conformity value used as the most suitable roadmap, which in this study is the Process Roadmap which then measures the level of maturity of each process area (Process Area Organizational Process Focus, Process Area Organizational Focus Definition, Process Area Measurement and Analysis, Process Area Causal Analysis and Resolution, Process Area Process and Product Quality Assurance). Recommendations are given based on the results of calculating the level of maturity of each Process Area so that the suggestions given can be used as appropriate and sustainable corrective measures for the relevant agencies.